2010
DOI: 10.1002/hed.21490
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical thyroid remnant estimation by 99mTc‐pertechnetate scintigraphy predicts radioiodine ablation effectiveness in patients with differentiated thyroid carcinoma

Abstract: The (⁹⁹m) Tc-pertechnetate scintigraphy is a simple and feasible tool to evaluate thyroid remnants and to predict radioiodine ablation results in patients with DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
3
18
0
1
Order By: Relevance
“…The advantages of pertechnetate over 123 I are widely available, inexpensive with long enough half-life and easiness to prepare. There are some literatures demonstrating the roles of 99m Tc-pertechnetate in the detection of post-thyroidectomy remnant and/or metastasis [18][19][20][21][22]. From a previous study, the main problems of 99m Tc-pertechnetate are its low specificity, possibly due to lack of anatomical localization outside thyroid bed, and low negative predictive value [18].…”
Section: Introductionmentioning
confidence: 96%
“…The advantages of pertechnetate over 123 I are widely available, inexpensive with long enough half-life and easiness to prepare. There are some literatures demonstrating the roles of 99m Tc-pertechnetate in the detection of post-thyroidectomy remnant and/or metastasis [18][19][20][21][22]. From a previous study, the main problems of 99m Tc-pertechnetate are its low specificity, possibly due to lack of anatomical localization outside thyroid bed, and low negative predictive value [18].…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies have reported that sequential measurement of the basal serum Tg level is more effective in detecting the functional remnant of the thyroid gland after total excision [1, 2]. The 99 m Tc pertechnetate scintigraphy is a simple and feasible tool to evaluate the thyroid remnants after thyroidectomy [3]. The unstimulated baseline Tg values during TSH suppression in total thyroidectomy cases were below 0.5 ng/mL by 6 months postoperatively, and sensitive for absence of thyroid remnant [4].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are known to affect the success of thyroid remnant ablation [6][7][8]. The extent of remnant thyroid tissue is one of the most important factors that influence the outcome of ablation [6,9]. Previous studies have demonstrated that a preablative diagnostic 131 I scan or thyroid bed uptake measurements can be used to evaluate the amount of thyroid remnant [7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of remnant thyroid tissue is one of the most important factors that influence the outcome of ablation [6,9]. Previous studies have demonstrated that a preablative diagnostic 131 I scan or thyroid bed uptake measurements can be used to evaluate the amount of thyroid remnant [7,[9][10][11][12]. As a stunning effect can be caused by a diagnostic radioiodine scan using 131 I, 123 I, or 99m Tc pertechnetate scans are preferred for evaluating the amount of remnant thyroid tissue [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation